Comparative pharmacokinetics of a proliposome formulation of Ginkgo biloba extract and Ginaton in rats by a sensitive ultra performance liquid chromatography-tandem mass spectrometry method - Zheng, B.; Xing, G.; Bi, Y.; Yan, G.; Wang, J.; Cheng, Y.; Ashraf, M.A.; Xie, J. (Elsevier, 2016)
As a novel oral drug delivery system, proliposome was applied to improve the solubility of active components of Ginkgo biloba extract (GbE). There are currently few reports focusing on the pharmacokinetic characteristics of proliposome of GbE (GbP). A rapid and sensitive ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method for the simultaneous quantification of active components of GbP and a commercial tablet product (Ginaton) in rat plasma was developed and successfully validated. The method was applied to the comparative pharmacokinetic evaluation of GbP and Ginaton in rat plasma. The results indicated that GbP has a significant effect on absorption, elimination and bioavailability of flavonoids and terpenoid lactones in comparison with Ginaton. The obtained results would be helpful for evaluating the absorption mechanism in the gastrointestinal tract in pharmacokinetic level and guiding the development of the novel oral drug delivery system.